Основні центри православного релігійно-паломницького туризму Польщі - Патійчук, Віктор Олексійович; Patiichuk, Viktor O. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Узагальнено теоретичні положення щодо функціонування релігійно-паломницьких центрів різного рівня територіальної організації. Досліджено особливості розвитку православного паломництва в Польщі. Вивчено історичні передумови розвитку православного паломництва на польській території. Розкрито значення православних святинь країни для розвитку релігійної культури та популяризації паломництва серед населення. Розглянуто значення релігійно-паломницького туризму для розвитку економіки цієї держави. Проаналізовано особливості поширення основних міжнародних православних релігійно-паломницьких центрів на території країни. Досліджено головні православні релігійно-паломницькі центри Польщі й описано їхні головні святині. Акцентовано на основних проблемах та перспективах розвитку православного релігійно-паломницького туризму в Польщі у контексті функціонування міжнародного паломництва.

The theoretical positions concerning the functioning of religious-pilgrim centers of different levels of territorial organization are generalized. The peculiarities of the development of the Orthodox pilgrimage in Poland are explored. The historical preconditions of the development of the Orthodox pilgrimage on the Polish territory were studied. The significance of the Orthodox shrines of the country for the development of religious culture and popularization of pilgrimage among the population are revealed. The significance of religious pilgrimage tourism for the development of the economy of this state is considered. The peculiarities of distribution of the main international Orthodox religious-pilgrimage centers on the territory of the country are analyzed. The main Orthodox religious-pilgrimage centers of Poland are described and their main shrines are described. The main issues and perspectives of the development of Orthodox religious-pilgrimage tourism in Poland in the context of the operation of the international pilgrimage are emphasized.
The Main Centers of the Orthodox Religious Pilgrimage Tourism of Poland
Keywords: релігійно-паломницький туризм; сакральні об’єкти; паломництво; релігійно-паломницький центр; Польща; religious-pilgrimage tourism; sacred objects; pilgrimage; religious-pilgrimage center; Poland